1996
DOI: 10.1111/j.1432-1033.1996.0223h.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Magnesium Dependences of the Class I and Class II Aminoacyl‐tRNA Synthetases from Escherichia coli

Abstract: The magnesium dependences of the ATPJPP, exchange and tRNA aminoacylation of reactions were measured for six aminoacyl-tRNA synthetases (isoleucyl-, tyrosyl-and arginyl-tRNA synthetases from class I, and histidyl-, lysyl-and phenylalanyl-tRNA synthetases from class 11). The measured values were subjected to best-fit analyses using sum square error calculations between the data and the calculated curves in order to find the mode of participation of the Mg" and to optimize the sets of the kinetic constants.The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…These results based on crystallographic analysis are consistent with an independent study of the magnesium dependence of ATP/PPi exchange and aminoacylation reactions of three class I and three class II E.coli aminoacyl-tRNA synthetases. This confirmed that the magnesium dependence of class 2954 I and class II synthetases is distinct, one magnesium being required for class I and three for the class II enzymes (Airas, 1996).…”
Section: Atp Bindingsupporting
confidence: 65%
“…These results based on crystallographic analysis are consistent with an independent study of the magnesium dependence of ATP/PPi exchange and aminoacylation reactions of three class I and three class II E.coli aminoacyl-tRNA synthetases. This confirmed that the magnesium dependence of class 2954 I and class II synthetases is distinct, one magnesium being required for class I and three for the class II enzymes (Airas, 1996).…”
Section: Atp Bindingsupporting
confidence: 65%
“…et al, 1974). Recent kinetic studies of class I and class II aaRS from E. coli are consistent with these results (Airas, 1996) ions since an Arg (Arg259 in HisRSec) substitutes for the third ion, as described above. Arg259, part of the highly conserved Histidine A motif (Figures 2, 4), is critical for HisRS activity; mutating it to glutamine, lysine (Rühlmann et al, 1997) or histidine reduces the activity by several orders of magnitude without affecting histidine or ATP binding.…”
Section: Mechanism Of Enzyme Actionsupporting
confidence: 64%
“…As LeuRS is a class I aaRS, Mg 2+ is not involved in aminoacylation of LeuRS directly [24]. Besides, only the free form Mg 2+ was considered in the aminoacylation assay buffer condition; effects of complex form Mg 2+ bound by ATP, AMP and pyrophosphate were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoacylation of Ec tRNA Leu (CAG) was assayed as described in [7] except that [Mg 2+ ]/[tRNA] was increased from 1:1 to 15:1, which was calculated based on concentration of the free Mg 2+ [24].…”
Section: Methodsmentioning
confidence: 99%